2015
DOI: 10.1007/s12275-015-4660-0
|View full text |Cite
|
Sign up to set email alerts
|

Communities of ammonia oxidizers at different stages of Spartina alterniflora invasion in salt marshes of Yangtze River estuary

Abstract: Spartina alterniflora, an aggressive invasive plant species at the estuarine wetlands of China's coasts, has become a major threat to the natural ecosystems. To understand its potential influence on nitrification processes, the community structures and abundance of ammonia-oxidizing archaea (AOA) and ammonia-oxidizing bacteria (AOB) were investigated using 454-pyrosequencing and quantitative real-time PCR (qPCR) in S. alterniflora invading salt marsh sediments at the Yangtze River estuary in Chongming island, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…The amoA gene obtained in the present study and other five pyrosequencing studies (sediments from Changjiang Estuary and Hangzhou Bay, soils from Minami-Daito Island and Ny-Ålesund) ( Hayashi et al, 2015 ; Tago et al, 2015 ; Xia et al, 2015 ; Zhang et al, 2015 , 2016 ) were trimmed as reported above. The remaining high-quality sequences were clustered into 280 OTUs (for AOA) and 201 OTUs (for AOB) at 97% similarity levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amoA gene obtained in the present study and other five pyrosequencing studies (sediments from Changjiang Estuary and Hangzhou Bay, soils from Minami-Daito Island and Ny-Ålesund) ( Hayashi et al, 2015 ; Tago et al, 2015 ; Xia et al, 2015 ; Zhang et al, 2015 , 2016 ) were trimmed as reported above. The remaining high-quality sequences were clustered into 280 OTUs (for AOA) and 201 OTUs (for AOB) at 97% similarity levels.…”
Section: Discussionmentioning
confidence: 99%
“… UPGMA clustering of AOA (A) and AOB (B) community compositions in previous studies and in the present study. RSB- ∗ , CJE- ∗ , HZB- ∗ , MD- ∗ , and NA- ∗ indicate sequences from this study, Changjiang Estuary ( Xia et al, 2015 ), Hangzhou Bay ( Zhang et al, 2015 , 2016 ), Minami-Daito Island ( Hayashi et al, 2015 ) and Ny-Ålesund ( Tago et al, 2015 ), respectively. …”
Section: Discussionmentioning
confidence: 99%
“…For the high-throughput sequencing data analyses, data processing was similar to that reported by Xia et al (2015) and Zeleke et al (2013a). Briefly, short or lowquality sequences were removed by visualizing the quality of the postsequencing data with MOTHUR software, ver.…”
Section: Data Processing and Statistical Analysismentioning
confidence: 99%
“…Root exudates are predicted to significantly alter the microbial community by affecting pH values (Xia et al, 2015). Soil pH is the strongest factor contributing to soil microbial community differences (Xiao et al, 2017;Liang et al, 2019).…”
Section: Figurementioning
confidence: 99%